Hipercubo : uma experiência pedagógica com o jogo na tematização da cultura corporal - Silva Júnior, Joeser Álvares da (2023)
The present study discusses the objectives and contents of Physical Education in schools from a critical and transformative perspective. To support these discussions, renowned authors in the field of national Physical Education were consulted, as well as the investigation of games as a phenomenon in themselves and applied in teaching and learning contexts. The main objective of the research is to understand the use of learning games as a strategy for teaching "bodily activity" in Physical Education classes in a municipal elementary school in Ji-Paraná - Rondônia. Specific objectives include: 1. Discuss the relationship between teaching to do and teaching about doing in Physical Education; 2. Analyze gamification as an auxiliary teaching resource for engaging students in teaching and learning processes; 3. Apply learning games as teaching resources for school subjects; 4. Implement a learning game as a didactic strategy for thematizing the contents of the body movement culture in a municipal elementary school in Ji-paraná, Rondônia. This research has a qualitative approach of the action research type. Systematic and unsystematic observation, as well as semi-structured interviews, were used as data collection instruments. The study was conducted at Menino Jesus Municipal School of Infant and Elementary Education, located in Ji-Paraná/RO. The participants were fifth-grade students in the afternoon period. The results indicate that the educational game Hypercube can be effective in fixing learning and eliciting meaningful experiences, but it is only a tool available to the teacher. In the children's sphere, games have their own purpose, so the educator who uses games as a means operates in a universe of probabilities. However, the teacher can create an inducing environment to increase the chances of students learning something meaningful. Therefore, it is understood that, beyond methodology, solid objectives should be established to guide teaching actions for the integral formation of students.